Studies on Propagation of Bael (Aegle marmelos L.) under Jhargram Conditions - S N Ghosh (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2012)
To work out the optimum time and method for commercial multiplication of bael (Aegle marmelos L.), an investigation was carried out in 2007 and 2008 at a private nursery in Jhargram of Paschim Midnapur, West Bengal. Results revealed that grafting in March should be done under propagation-shed condition. During shortage of scion material, chip budding can be practiced from 20th to 30th March, under partial shade. For raising the orchard in-situ, chip budding should be done at the onset of monsoon (10th to 25th June) on two-year old seedlings, which should have been pruned the previous October.